Osthole‐loaded N‐octyl‐O‐sulfonyl chitosan micelles (NSC‐OST) inhibits RANKL‐induced osteoclastogenesis and prevents ovariectomy‐induced bone loss in rats. Issue 7 (3rd March 2020) - Wang, Lining; Zheng, Suyang; Huang, Guicheng; Sun, Jie; Pan, Yalan; Si, Yuhao; Tu, Pengcheng; Xu, Guihua; Ma, Yong; Guo, Yang
Abstract: Osthole (OST), a derivative of Fructus Cnidii, has been proved to have potential anti‐osteoporosis effects in our recent studies. However, its pharmacological effects are limited in the human body because of poor solubility and bioavailability. Under the guidance of the classical theory of Chinese medicine, Osthole‐loaded N‐octyl‐O‐sulfonyl chitosan micelles (NSC‐OST), which has not previously been reported in the literature, was synthesized in order to overcome the defects and obtain better efficacy. In this study, we found that NSC‐OST inhibited on the formation and resorption activity of osteoclasts through using a bone marrow macrophage (BMM)‐derived osteoclast culture system in vitro, rather than affecting the viability of cells. We also found that NSC‐OST inhibited osteoclast formation, hydroxyapatite resorption and RANKL‐induced osteoclast marker protein expression. In terms of mechanism, NSC‐OST suppressed the NFATc1 transcriptional activity and the activation of NF‐κB signalling pathway. In vivo, ovariectomized (OVX) rat models were established for further research. We found that NSC‐OST can attenuate bone loss in OVX rats through inhibiting osteoclastogenesis. Consistent with our hypothesis, NSC‐OST is more effective than OST in parts of the results. Taken together, our findings suggest that NSC‐OST can suppress RANKL‐induced osteoclastogenesis and prevents ovariectomy‐induced bone loss in rats and could be considered a safe and more effective anti‐osteoporosis drug than OST.